Felicity Analysis on The Main Character in The Game Movie Resident Evil 2 Remake - Setyawan, Ilham; Cahyaningrum, Ika Oktaria (Allure Journal, 2023)
The purposes of this research are for knowing what kind felicity condition within the conversation by using Leon as a limitation. Beside to classifying the type of felicity condition, the researchers also want to know what is the impact if the felicity condition is not fulfilled inside the conversation. This research is using descriptive qualitative method to get the data. In accordance with Creswell's theory, the researchers only use Resident Evil 2 Remake as an object and it will be used as the data in this research. To validating the data, the researchers using Theory Triangulation, the theory said to use an expert theory to analyzing the data and the researchers here is using Yule as a base to analyzing and classifying the type of felicity condition that will eventually become a complete data to make a conclusion. This research has 5 types of felicity condition according to the theory that the researchers use. The types are General Condition (25%), Content Condition (23,4%), Preparatory Condition (10%), Sincerity Condition (30%), and Essential Condition (11,6%). The percentage above are from analyzing 60 data inside the conversation that Leon have and some other characters who had conversation with Leon. Beside the types, there is also an impact which exist because the utterance become infelicitous. The impact is misinvocation (38%), misexecution (31%), and abuse (31%). These impacts here cause a different result from what the speaker intended